Redesigning courses for online delivery design, interaction, media & evaluation - Parker, Robyn E. (Cutting-edge technologies in higher education ;, 2013)
This volume examines key considerations for effective online course redesign. Using a 4-phase approach, Redesigning Courses for Online Delivery informs thinking, inspires creativity, and structures decisions to drive the development of high quality online learning experiences. Both scholarly and practical, it provides a comprehensive approach to redesign useful to novices and veterans alike.